2008
DOI: 10.1089/cap.2007.0027
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obsessive-Compulsive Disorder Presenting as Schizophrenia Spectrum Disorders

Abstract: Obsessive compulsive disorder (OCD) is a highly heterogeneous disorder, presenting with a wide array of symptoms. Sometimes, OCD can appear to be psychotic in nature, with periods of loss of insight or the emergence of paranoid ideas. Likewise, individuals with schizophrenia spectrum disorders (SSDs), including schizophrenia or schizo-affective disorder, can have obsessive-compulsive or "obsessive-compulsive like" symptoms. The complexities of differentiating obsessive-compulsive symptoms from true psychotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(9 reference statements)
0
12
0
1
Order By: Relevance
“…Poor insight in OCD causes patients not to recognize their symptoms as a problem and results in reduced treatment motivation and treatment success. Therefore OCD patients with poor insight may be misdiagnosed or may not seek treatment [62,64].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Poor insight in OCD causes patients not to recognize their symptoms as a problem and results in reduced treatment motivation and treatment success. Therefore OCD patients with poor insight may be misdiagnosed or may not seek treatment [62,64].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Det kan til tider vaere vanskelig å differensiere mellom denne formen for tvang og påtrengende tanker og ritualistisk atferd som ses hos barn med tvangslidelser (OCD) (69). Hallusinasjoner og vrangforestillinger er som regel ikke til stede ved OCD, men det er rapportert om tilfeller der det som ser ut til å vaere schizofreni, har vist seg å vaere en tvangslidelse (58). Som regel vil barn med OCD erkjenne symptomene som irrasjonelle produkter av egen tenkning og ønske å bli kvitt dem, mens psykosesymptomer oppstår mer uavhengig av pasientens kognitive prosess (69).…”
Section: Komorbiditet Ved Tidlig Debutunclassified
“…Subsequent to a randomized, double-blind, placebo-controlled trial in 1986, the first-generation antipsychotic trifluoperazine was given FDA approval for short-term treatment of generalized non-psychotic anxiety (Gao, Muzina, Gajwani & Calabrese, 2006). Specifically, antipsychotics may be beneficial in OCD, which many have noted shares some features of a psychotic or delusional process (Bellino, Patria, Ziero & Bogetto, 2005;Kozak & Foa, 1994;Rodowski, Cagande & Riddle, 2008). Patients with OCD have classically had insight into the illogical nature of their thoughts or behaviors; the criteria for OCD in the current version of the Diagnostic and Statistical Manual of Mental Disorders includes that the patient recognizes the obsessions or compulsions are excessive or unreasonable, although this does not apply to children (DSM-IV-TR; APA, 2000).…”
Section: Risperidonementioning
confidence: 99%
“…Since Amy is a child, the DSM qualifier of requiring insight does not apply to making the diagnosis of OCD, yet the comparisons to a psychotic process remain. Studies have suggested OCD patients bordering on the psychotic may be the group most responsive to antipsychotic augmentation (Rodowski et al, 2008). Furthermore, there is some evidence to suggest that some early cases of schizophrenia-spectrum disorders may initially present with obsessive-compulsive symptoms, and vice versa (Niendam, Berzak, Cannon & Bearden, 2009;Rodowski et al, 2008;Tumkaya et al, 2009).…”
Section: Risperidonementioning
confidence: 99%
See 1 more Smart Citation